The Project Ahead: Some Thoughts on Developing a Popular Music Curriculum - Théberge, Paul (Canadian University Music Review / Revue de musique des universités canadiennes, 2000)
Arguing that past attempts at introducing popular music into the curriculum have taken place primarily at the level of the individual course, the author argues that a more extensive and integrated approach to developing academic programs in popular music is now needed. The model for such a program must be both multidisciplinary and interdisciplinary in character and must include the full participation of departments and faculties of music. Consideration is given to the special demands placed on music programs in terms of the need to rethink the structures and pedagogical practices associated with present-day higher education in music.